The New Yugoslav Criminal Code - Donnelly, Richard C. (1952)
THE new Yugoslav Criminal Code, which became effective on July 1, 1951, is of twofold interest to students of criminal law. First of all, it is a contemporary specimen of codification. More importantly, it is an instrument reflecting the ideological assumptions of a Communist State. The achievement of justice in criminal cases depends upon four interacting variables: personnel, administration, procedure, and the substantive law of crimes. Criminal law reformers have been concerned chiefly with the first three. For example, there have been important studies of crime causation and legal responsibility. The revulsion against retribution as the aim of punishment- generated by Nineteenth Century Humanitarianism-has been fortified by the new insights into human motivation revealed by the behavior sciences. The development of probation, parole, and other release procedures as alternatives to penal commitment, and the individualization of sentencing and treatment, are other trends of significance. The American Law Institute's Code of Criminal Procedure and the recent Federal Rules of Criminal Procedure have given impetus to needed improvements in criminal procedure. In the end, however, criminal justice must rest upon a satisfactory substantive law of crimes. Although Great Britain and the United States stand in the vanguard of the penological reform movement, the forces directing this movement have shown little interest in the criminal law proper. In fact, the substantive law of crimes in the United States remains uncertain, obscure, formally defective, inconsistent and antiquated. If by codification is meant the effort to simplify, synthesize and systematize law by the positive legislative formulation of inclusive and operationally defined principles, Great Britain and the United States have lagged far behind Continental countries. There are compilations of statutes, sometimes designated as codes and sometimes not, but these are rarely systematic bodies of law. There have been sporadic and haphazard amendments to the statutes but these have been mostly patch-work jobs. Except for the 1942 Louisiana Code, there have been but few major efforts to codify the substantive law of crimes